PERSEPSI MAHASISWA UNIVERSITAS RIAU TENTANG PERANAN SATPAM DI KAMPUS UNIVERSITAS RIAU - Afarat, Munzir; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak:This research is motivated by the problem of security and comfort that is disturbed in the Riau University campus environment which is caused by people who commit acts that violate the law and could be detrimental to others in the campus area. The formulation of the problem in this study is how is the perception of Riau university students about the role of security guards at the Riau University campus. The purpose of this study was to determine the perceptions of Riau university students about the role of security guards at the Riau University campus. Benefits of research results for students to provide an overview of the role of security guards on duty on campus and in the future students can work together with security guards to create security comfort together This research method is quantitative descriptive, data collection instruments used in this study are questionnaires consisting of 23 questions with 6 subindicators. The population in this study were students of Riau University. The sample in this study was taken using a purposive sampling technique. Based on the results of the research conducted,concluded that overall the data regarding the perception of Riau University students about the role of security guards on the University of Riau campus are in the